(untitled) (Revista de Ciências Agroveterinárias, 2019)
Accuracy in meeting nutritional requirements has great importance in quail nutrition however there is a lack of consensus on crude protein (CP) recommendations specific for European quails. The present study aimed to define crude protein requirements for European quails on performance and carcass characteristics. A completely randomized design was used in a 5 × 2 factorial scheme, with five CP levels for male and female quails. In the starting phase (1 to 21 days) it was used 1,800 quails and CP levels were 20,0, 22,5, 25,0, 27,5 and 30,0%, with six replicates containing 30 birds each. In the growth phase (22 to 45 days) it was used 1.620 quails and CP levels were 17,5, 19,5, 22,0, 24,5 and 27,0%, with six replicates containing 27 birds each. Theirs d was a corn soybean based diet in grounded form. The performance of the quails was evaluated in the end of each experimental phase and carcass yield in 45 days. Weight gain and feed conversion ratio was higher for 25,50% and 27,06% respectively, regardless of gender, in 21 days. In the growth phase, it was observed just gender effect in which female quails had higher performance. For carcass characteristics, male quails obtained higher carcass and dorse yield and female quails higher breast, liver and gizzard yields.